2021
DOI: 10.3389/fgene.2021.669328
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Reduction Can Help to Improve the Identification of Antimicrobial Peptides and Their Functional Activities

Abstract: Antimicrobial peptides (AMPs) are considered as potential substitutes of antibiotics in the field of new anti-infective drug design. There have been several machine learning algorithms and web servers in identifying AMPs and their functional activities. However, there is still room for improvement in prediction algorithms and feature extraction methods. The reduced amino acid (RAA) alphabet effectively solved the problems of simplifying protein complexity and recognizing the structure conservative region. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…As depicted in Figure 7 , numerous models currently specialize in AMP attribute prediction, ranging from initial single activity prediction to multi-attribute prediction. In our Diff-AMP framework, we have integrated leading AMP attribute prediction models, including AMAP [ 62 ], AMPfun [ 63 ], CAMP [ 64 ], DbAMP2.0 [ 65 ], DRamp [ 66 ], iamp-2l [ 67 ], iamp-CA2L [ 44 ], iamp-RACC [ 68 ], MLAMP [ 69 ], multi-AMP [ 47 ] and IAMPCN [ 53 ]. This capability allows the Diff-AMP framework to extensively predict AMP properties, encompassing over 20 attributes such as antibacterial, anti-Gram-positive, anti-Gram-negative, antifungal, antiviral and more.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted in Figure 7 , numerous models currently specialize in AMP attribute prediction, ranging from initial single activity prediction to multi-attribute prediction. In our Diff-AMP framework, we have integrated leading AMP attribute prediction models, including AMAP [ 62 ], AMPfun [ 63 ], CAMP [ 64 ], DbAMP2.0 [ 65 ], DRamp [ 66 ], iamp-2l [ 67 ], iamp-CA2L [ 44 ], iamp-RACC [ 68 ], MLAMP [ 69 ], multi-AMP [ 47 ] and IAMPCN [ 53 ]. This capability allows the Diff-AMP framework to extensively predict AMP properties, encompassing over 20 attributes such as antibacterial, anti-Gram-positive, anti-Gram-negative, antifungal, antiviral and more.…”
Section: Resultsmentioning
confidence: 99%
“…With each evaluation method, there were up to 18 different grouping methods, from which up to 673 schemes were created. This method was applied in classification of human enzymes and in classification of antimicrobial peptides . Another way of grouping amino acids was proposed by Takabatake et al in which the BLOSUM62 matrix was used to calculate the number of similarity scores between amino acids prior to calculating the correlation coefficients of each pair of amino acids and grouping the amino acids using hierarchical clustering.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-treatment of embryos with SIAMP and infected with IBV showed a remarkable reduction in mortality. Though the authors of this study did not present the characterization of the antiviral mechanism, they suggested that SIAMP might play a role during virus attachment to the cell surface, thus limiting IBV infection (93). Mannose binding lectin (MBL) is well known as an antiviral agent (94).…”
Section: Use Of Virucidal Drugs Against Ibv Infectionmentioning
confidence: 96%